Autonomic nervous regulation in preschool children with neurotic symptoms - Konkabayeva, A.Ye.; Bodeeva, R.T.; Oleksyuk, Z.Ya.; Danilenko, M. (Fundamental and Experimental Biology, 2017)
The article evaluates the results of autonomic nervous regulation in preschool children with different psychological status through the analysis of heart rate variability. We examined 127 children aged 3,8–5,5 years. The average statistical indices describing the regulation of the heart rhythm in preschool children with neuroses, predoneuroses, anxiety and normally developing have been determined. Preschoolers with neurosis were characterized by significantly higher temporal HRV values: heart rate, heart rate, activity index of regulatory systems, SI. The changes in the regulation of the heart rhythm have been established, which testify to the strengthening of the sympathetic contour of regulation in children with neurosis, the immaturity of the parasympathetic department of the central nervous system, reflect the stress of the regulatory systems, and also indicate a decrease in the reserve capacities of the organism.